Computed Tomography Examination Reveals Brain Lesions in Guangzhou AIDS Patients (Global Journal of Medical Research, 2016)
Cranial computed tomography (CT) plays an important role in the diagnosis of AIDS. However, our understanding of the CT scan images on the diagnosis or evaluating treatment results has not yet been completed. In this study, we conducted an investigation on the usefulness of cranial CT examination in diagnosing HIV patients. Among them, 34 AIDS patients tested positive for brain lesions indicated by cranial CT scan examination. Patients who had AIDS with brain lesions were primarily diagnosed with tuberculous meningitis (TBM), HIV encephalitis (HIVE), cerebral toxoplasmosis (CT) and cryptococcal meningitis (CM). Furthermore, we thoroughly compared the characteristics of various brain lesions in CT images so that it could be helpful for future diagnoses and treatment evaluations of AIDS with brain lesions. Additionally, we demonstrated that a count of less than 50 CD4+ T lymphocytes primarily occurred in the TBM and HIVE groups, thus resulting in higher mortality.
Keywords: AIDS brain lesions; CT scan; tuberculous meningitis; HIV encephalitis; cerebral toxoplasmosis and cryptococcal meningitis